MP38: Are we missing pulmonary embolism in acute exacerbations of chronic obstructive pulmonary disease presenting to the emergency department? Multicenter insights into incidence of concomitant disease and yield of testing. (May 2019) - Moussienko, D.; Lang, D.; Skeith, L.; Lang, E.
Abstract : Introduction : Patients with Chronic Obstructive Pulmonary Disease (COPD) often present to the ED with acute exacerbations (AE-COPD) of the disease. A potential occult yet fatal disease that might contribute or accompany an AE-COPD presentation is a pulmonary embolism (PE). Previous studies have investigated and report rates of PE in up to 29% of patients presenting with AE-COPD. Misdiagnoses of PE leads to poor outcomes, however, over-testing for PE also presents with substantial risks to the patient and strain on acute care resources. The goal of this study was to pragmatically identify the prevalence and 30-day incidence of PE in patients presenting with AE-COPD to EDs, as well as the burden and yield of PE investigations.Methods : We conducted a retrospective analysis of extracted data for patients □50 years old presenting to one of four emergency departments in Calgary with an AE-COPD since 2013. Patients with a history of outpatient anticoagulation therapy from a community pharmacy were excluded. Each patient chart was reviewed to identify a diagnosis of PE during the admission for an AE-COPD, or 30 days post discharge from an AE-COPD admission or ED presentation. An AE-COPD diagnosis was defined as a primary.Results : A total of 9554 AE-COPD ED patient visits were included in the study. 0.69% (95%CI 0.54 to 0.88) were identified to have a PE. 26 of the 66 (39.4%) were diagnosed during an AE-COPD inpatient admission, while 43 (65.2%) were diagnosed within 30 days post-discharge from an AE-COPD admission or ED presentation. Since 2016, 7.4% of AE-COPD patients underwent a CT-PE, while 16.7% underwent a d-dimer. The most common chief complaint in PE patients was dyspnea (75.8%). The mean age of the PE diagnosed was 73.4, with nearly equal representation of both sexes. Many patients had underlying comorbidities, such as hypertension, diabetes, and cancer of various sites, all of which are risk factors for developing a PE.Conclusion : The prevalence and 30-day incidence of PE in AE-COPD patients appears to be lower than what was previously reported in the literature. Despite this, a significant proportion of AE-COPD patients were exposed to the risks and burden of a PE work up, with low diagnostic yield. PE investigations in AE-COPD should be used selectively and could inform a quality improvement indicator. A future prospective study would drastically contribute to whether a PE clinical work up should be recommended and of value to patients.